Sand Grain Sizes and Shapes in Eolian Bedforms at Gale Crater, Mars. Issue 18 (23rd September 2018) - Weitz, Catherine M.; Sullivan, Robert J.; Lapotre, Mathieu G. A.; Rowland, Scott K.; Grant, John A.; Baker, Mariah; Yingst, R. Aileen
Abstract: We measured sand sizes and shapes on diverse eolian bedforms in Gale crater to help constrain models of eolian sediment transport on Mars. All grains are subangular to rounded with circularities of ~0.93–0.97, indicating an extensive abrasion history. There are two types of active bedforms based on grain size: (1) ripples composed of 50‐ to 150‐μm grains and (2) ripples that also include 250‐ to 500‐μm grains along their crests, in some cases with small amounts of even coarser grains (up to 1.4 mm). The smallest grain sizes (50–150 μm) are volumetrically the most abundant at all active bedforms. Inactive bedforms have surfaces of 350‐ to 2, 000‐μm grains with finer‐grained interiors, consistent with observations made by rovers at other landing sites. Grains coarser than ~300 μm are less prone to mobilization driven by smaller saltating grains, making bedforms with concentrations of coarser grains more susceptible to surface stabilization and inactivity. Plain Language Summary: We used microscopic images taken by a camera on the Curiosity rover at Mars to measure the shapes and sizes of sand grains. There are two types of active ripples that we identified based upon grain size: those that have grain sizes between 50 and 150 microns and those with coarser grains between 250 and 500 microns. Most of the grains on the active Bagnold dunes are very fine sand, except at the crests of larger ripples where the grains tend to be larger. The grains are circular and rounded, indicating that they have experienced an extensive abrasion history. Inactive ripples have coarser grains (350–2, 000 μm) armoring finer interior grains, some of which could be locally derived from the Stimson sandstone and Murray Formation outcrops. On Earth, the physical properties of grains partly control bedform morphology and are closely linked with mobility. Because these same principles are expected on Mars, it is important to know sand grain size and shape distributed across diverse ripple morphologies to help constrain models of martian bedform formation. Key Points: Sand grains on eolian bedforms on Mars vary in size and shape depending upon whether the bedform is active or inactive The size distribution of most active sands is narrow and very fine (50‐150 micrometers) unless on a coarse‐grained (250‐500 micrometers size) ripple Coarse‐grained ripples at Gale have similar grain sizes to those at both Gusev crater and Meridiani Planum landing sites